2022
DOI: 10.1002/mnfr.202100653
|View full text |Cite
|
Sign up to set email alerts
|

Diets Containing Egg or Whey Protein and Inulin Fiber Improve Energy Balance and Modulate Gut Microbiota in Exercising Obese Rats

Abstract: Scope: Dietary protein, prebiotic fiber, and exercise individually have been shown to aid in weight loss; however less is known of their combined effects on energy balance. The effects of diets high in protein and fiber, with exercise, on energy balance, hormones, and gut microbiota, were determined. Methods and Results: Obese male rats were fed high-fat diets with high protein and fiber contents from egg protein and cellulose, egg protein and inulin, whey protein and cellulose, or whey protein and inulin, tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…This experiment then evaluated the additional beneficial effects dietary fiber could have in exercising rats. The results showed that both inulin-containing diets decreased food intake and weight gain and improved glycemic control more so than cellulose-containing diets, and this was similar to previous work in nonexercised rats [47 ▪ ]. Diet type explained 46% of the total variation in cecal microbiota composition, and plasma butyric acid, a short-chain fatty acid, was the plasma metabolite that was most strongly associated with the predicted functional pathways identified from metagenomic sequencing [47 ▪ ].…”
Section: Effects Of Dietary Fiber On the Gut Microbiotasupporting
confidence: 83%
See 1 more Smart Citation
“…This experiment then evaluated the additional beneficial effects dietary fiber could have in exercising rats. The results showed that both inulin-containing diets decreased food intake and weight gain and improved glycemic control more so than cellulose-containing diets, and this was similar to previous work in nonexercised rats [47 ▪ ]. Diet type explained 46% of the total variation in cecal microbiota composition, and plasma butyric acid, a short-chain fatty acid, was the plasma metabolite that was most strongly associated with the predicted functional pathways identified from metagenomic sequencing [47 ▪ ].…”
Section: Effects Of Dietary Fiber On the Gut Microbiotasupporting
confidence: 83%
“…Several studies have been investigating inulin, a soluble fiber, as a potential dietary supplement to alleviate the sequelae of high fat diets and obesity. A combination of egg or whey protein with either cellulose (insoluble fiber) or inulin (soluble fiber) was evaluated for improving weight gain and obesity-associated metabolic alterations in in obese rats fed high fat diets and exercised on a treadmill [47 ▪ ]. This experiment then evaluated the additional beneficial effects dietary fiber could have in exercising rats.…”
Section: Effects Of Dietary Fiber On the Gut Microbiotamentioning
confidence: 99%
“…Feeding 750 mg/kg of EWP hydrolysate to obese rats significantly reduced the relative abundance of Lactobacillus and decreased lactate content . When obese rats were fed insulin and EWP together, the SCFA level in their bodies also increased . Feeding ovotransferrin-derived peptides IRW and IQW to obese mice decreased F/B values but did not affect the relative abundance of Actinobacteriota, Proteobacterota, and Deferribacterota …”
Section: Regulation Of Gut Microbiota By Ewpmentioning
confidence: 93%
“…129 When obese rats were fed insulin and EWP together, the SCFA level in their bodies also increased. 130 Feeding ovotransferrin-derived peptides IRW and IQW to obese mice decreased F/B values but did not…”
Section: Regulation Of Gut Microbiota In the Damagedmentioning
confidence: 98%
“…A growing body of evidence suggests that the gut microbiota is a bridge to connect the external environment and the host homeostasis. On the one hand, the composition of gut microbiota can be affected by region (20), race/ethnicity (21), diet (22)(23)(24), and host genetics (6). For example, geographical location has been suggested to be closely associated with gut microbiota variation (20), and race/ethnicity (22) or its correlates such as diet and socioeconomic status have important influences on gut microbiota.…”
Section: Introductionmentioning
confidence: 99%